Cushing's Syndrome Pathophysiology, Diagnosis and Treatment - Bronstein, Marcello D.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Cushing´s syndrome is a relatively rare clinical disorder that is associated with many co-morbidities such as systemic hypertension, diabetes, osteoporosis, impaired immune function and growth impairment in children, all of which severely reduce quality of life and life expectancy. Cushing’s Syndrome: Pathophysiology, Diagnosis and Treatment reviews the difficulties in distinguishing Cushing’s syndrome from these and other common conditions, such as central obesity, menstrual irregularity and depression. It also provides state-of-the-art information on various strategies to establish the diagnosis of Cushing’s syndrome and the differential diagnosis among its diverse etiologies, as well as therapeutic approaches. Additionally, a range of conditions that represent challenges for the diagnosis and treatment--such as renal failure, pediatric age, cyclic hypercortisolism, and pregnancy--are covered in detail. A valuable resource not only for endocrinologists but also internal medicine physicians, gynecologists, pediatricians, , pituitary surgeons and urologists, Cushing’s Syndrome: Pathophysiology, Diagnosis and Treatment provides insights by experts that will help all physicians dealing with Cushing´s syndrome to expand their knowledge about the condition and provide targeted, comprehensive care.
Physiology and Pathophysiology of the HPA axis -- Etiologies of Cushing´s syndrome -- Pathogenesis of corticotropic tumors -- Pathogenesis of adrenocortical tumors -- Clinical features of Cushing´s syndrome -- Laboratorial diagnosis of Cushing´s Syndrome: Differential diagnosis with pseudo-Cushing´s conditions as obesity, alcoholism and depression -- Laboratorial diagnosis of Cushing´s syndrome: Differential diagnosis among the different causes of ACTH-dependent and ACTH-independent Cushing´s syndrome -- Imaging for the differential diagnosis of Cushing´s syndrome: MRI, CT and isotopic scanning -- Inferior petrosal sampling for the differential diagnosis of ACTH dependent Cushing´s syndrome -- ACTH-dependent Cushing syndrome: Treatment of Cushing´s disease -- Treatment of Cushings Syndrome: Surgical Treatment -- Adrenal-Directed Treatment Options for Cushing’s Disease -- Radiation Therapy and Stereotactic Radiosurgery for Cushing’s Disease -- Medical Management of Cushing’s syndrome -- ACTH-dependent Cushing syndrome: Clinical and diagnostic aspects, and treatment approaches for ectopic Cushing´s syndrome -- Revisiting the Nelson’s syndrome: Corticotroph Tumor Progression after bilateral adrenalectomy in Cushing’s disease -- ACTH-independent Cushing´s syndrome: Adrenocortical tumors -- ACTH-independent Cushing´s syndrome: Bilateral macronodular hyperplasia -- ACTH-independent Cushing´s syndrome: primary pigmented nodular adrenal disease in the context of Carney´s complex -- Glucocorticoid Resistance -- Post-operative replacement and assessment of HPA axis recovery in Cushing’s syndrome -- Special aspects of Cushing´s syndrome: Pregnancy -- Special aspects of Cushing´s syndrome: Childhood -- Special aspects of Cushing´s syndrome: Cyclic Cushing´s syndrome.
Keywords: Endocrinology .; Internal medicine; Oncology .; Pediatrics; Gynecology .; Neurosurgery; Endocrinology; Internal Medicine; Oncology; Pediatrics; Gynecology; Neurosurgery